2015
DOI: 10.1590/1415-52732015000200002
|View full text |Cite
|
Sign up to set email alerts
|

Food habits and risk of cardiovascular disease in schoolchildren from Ouro Preto, Minas Gerais

Abstract: OBJECTIVE: To investigate the relationship between food habits and risk factors for cardiovascular disease in schoolchildren of the city Ouro Preto, Minas Gerais. METHODS: A cross-sectional study was conducted in a population-based sample of 738 schoolchildren aged 6-14 years. A semi-structured questionnaire was used for collecting demographic, socioeconomic, biochemical, clinical, and anthropometric data. Food intake was determined by a food-frequency questionnaire. Food habits were evaluated according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…The prevalence of heart diseases has increased over the past two centuries and is now recognized as one of the primary causes of mortality and disability all over the world [1]. The mortality rate caused by the disease is higher in the developed and developing countries and the reports since 2011 have shown about 17 million deaths due to cardiovascular problems in the world [2]. Now, the disease imposes high costs on the community in the form of surgery, other therapeutic programs, controlling complications and disability of people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of heart diseases has increased over the past two centuries and is now recognized as one of the primary causes of mortality and disability all over the world [1]. The mortality rate caused by the disease is higher in the developed and developing countries and the reports since 2011 have shown about 17 million deaths due to cardiovascular problems in the world [2]. Now, the disease imposes high costs on the community in the form of surgery, other therapeutic programs, controlling complications and disability of people.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations indicated that a dietary pattern rich in red meat and processed meat is associated with cardiovascular disease, and the high consumption of meat can reduce the positive effects of fruits and legumes and this consequently leads to the risk of heart disease [10,11]. According to the results of various studies, nutritional status is highly emphasized [2,7]. Anthropometric indices such as BMI and waist circumference are also important factors in the incidence of CAD [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Em relação à frequência de consumo de diferentes tipos de alimentos, a pesquisadora também apontou redução na frequência de consumo de frutas, carnes processadas, hortaliças, raízes, tubérculos e derivados, pães, refrigerantes, preparações mistas, cereais e bebidas de baixa caloria para estudantes tanto de escolas privadas quanto de escolas públicas entre o período avaliado. Coelho et al (2015), por meio de estudo transversal realizado em Ouro Preto-MG com 738 crianças e adolescentes com idades variando entre 6 e 14 anos, também deduziram que, de modo geral, a alimentação dos estudantes apresentava qualidade insatisfatória, com reduzido consumo de alimentos saudáveis, visto que o score alimentar recomendado foi de apenas 16 pontos para as crianças e de 15 pontos para os adolescentes, em meio ao valor máximo de 50 que poderia ser obtido. Dentre os alimentos considerados saudáveis mais consumidos tinham-se o tomate e a alface do grupo das hortaliças; a banana, laranja e maçã do grupo das frutas; o arroz e o feijão do grupo dos cereais e leguminosas; o frango do grupo das carnes e os iogurtes de frutas e queijos de baixo teor de gorduras no grupo dos laticínios magros.…”
Section: Grau De Processamentounclassified
“…Logo, pessoas que apresentam maior massa corpórea podem ingerir uma quantidade maior destes compostos sem, necessariamente, ultrapassar os limites preconizados, enquanto indivíduos com menor peso podem apresentar uma menor ingestão para tais componentes e, mesmo assim, consumir nitrato e nitrito em quantidades superiores àquelas referentes à ingestão diária aceitável (BEMRAH;LARSSON et al, 2011) FERREIRA et al, 2019;SILVA et al, 2019). Entretanto, situações inversas também podem ser identificadas na literatura científica, na qual uma alimentação mais saudável, marcada pela presença de frutas e hortaliças é apontada por ser mais prevalente entre filhos de famílias com maiores rendimentos (COELHO et al, 2015;MARTINS et al, 2013;MOMM;HOFELMANN, 2014;SILVA et al, 2015). Há ainda pesquisas que não constatam associações entre renda e os tipos de alimentos consumidos por crianças e adolescentes, evidenciando que os maus hábitos alimentares se encontram generalizados na população brasileira (CORRÊA et al, 2017;MOLZ et al, 2019;MONTEIRO et al, 2020).…”
Section: Masculinounclassified